Lignin-based nano-enabled agriculture: A mini-review - Gigli, Matteo; Fellet, Guido; Pilotto, Laura; Sgarzi, Massimo; Marchiol, Luca; Crestini, Claudia (Frontiers in Plant Science, 2022)
Nowadays, sustainable nanotechnological strategies to improve the efficiency of conventional agricultural practices are of utmost importance. As a matter of fact, the increasing use of productive factors in response to the growing food demand plays an important role in determining the environmental impact of agriculture. In this respect, low-efficiency conventional practices are becoming obsolete. On the other hand, the exploitation of nanoscaled systems for the controlled delivery of fertilizers, pesticides and herbicides shows great potential towards the development of sustainable, efficient and resilient agricultural processes, while promoting food security. In this context, lignin ‒ especially in the form of its nanostructures ‒ can play an important role as sustainable biomaterial for nano-enabled agricultural applications. In this review, we present and discuss the current advancements in the preparation of lignin nanoparticles for the controlled release of pesticides, herbicides, and fertilizers, as well as the latest findings in terms of plant response to their application. Special attention has been paid to the state-of-the-art literature concerning the release performance of these lignin-based nanomaterials, whose efficiency is compared with the conventional approaches. Finally, the major challenges and the future scenarios of lignin-based nano-enabled agriculture are considered.